2022
DOI: 10.9734/ijpss/2022/v34i1931109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of FYM and Inorganic Fertilizers on Nutrient Content, Uptake and Quality Traits of Wheat (Triticum aestivum L.) under Indo-Gangetic Plain of Uttar Pradesh

Abstract: A field trial was conducted on sandy loam soil having low status of organic carbon and accessible nitrogen, medium in accessible phosphorous and high in accessible potassium at pot house of department of Soil Science and Agricultural Chemistry of C.S.A.U.A&T, Kanpur (campus) under Indo-Gangetic Plain zone of Uttar Pradesh, amid Rabi season of 2018-19. The experiment comprised of 5 treatment combinations in randomized block design with four replications consisted of T1: [Control], T2: [100% RDF], T3: [75% R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
(16 reference statements)
4
7
0
Order By: Relevance
“…Phosphate solubilizing bacteria (PSB) as bio-fertilizers have been found effective in solubilizing the fixed soil P and applied phosphates resulting in higher crop yields. The consequences of the current investigation are additionally in concurrence with the investigation of Agrawal et al [20], Jarvan et al [16], Choudhary et al [30], Panhwar et al [22] and Choudhary et al [14].…”
Section: Growth Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…Phosphate solubilizing bacteria (PSB) as bio-fertilizers have been found effective in solubilizing the fixed soil P and applied phosphates resulting in higher crop yields. The consequences of the current investigation are additionally in concurrence with the investigation of Agrawal et al [20], Jarvan et al [16], Choudhary et al [30], Panhwar et al [22] and Choudhary et al [14].…”
Section: Growth Parameterssupporting
confidence: 91%
“…. It is reported that high amount of zinc is contained in pollen and mostly zinc is inverted to seed only during seed formation and an application of zinc improves grain formation" [14].…”
Section: Introductionmentioning
confidence: 99%
“…) and harvest index (36.95 %) has been associated with the control plot. The results of the present investigation were also in agreement with the findings of Choudhary et al [11].…”
Section: Productivity Parameterssupporting
confidence: 94%
“…At present about 48.1% of Indian soils are rated as very low in available zinc [3]. Hence, present investigation was carried out to study the growth, yield and nutrient uptake behaviour of wheat to define optimum dose under integrated use of FYM [4].…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effect of FYM might be attributed to increased activities of heterotrophic bacteria and fungi in soil, which in turn increased the activity of soil enzymes responsible for the conversion of unavailable form of nutrients to available form. The similar beneficial effect of nutrient management in wheat are also reported by several scientist Menka et al, [12], Sheoran et al, [13] and Choudhary et al [14].…”
Section: Growth Parameterssupporting
confidence: 84%